2011
DOI: 10.1002/mrm.23294
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurement of cerebral blood flow and transit time with turbo dynamic arterial spin labeling (Turbo‐DASL): Application to functional studies

Abstract: A turbo dynamic arterial spin labeling (Turbo-DASL) method was developed to simultaneously measure cerebral blood flow (CBF) and blood transit time with high temporal resolution. With Turbo-DASL, images were repeatedly acquired with a spiral readout after small-angle excitations during pseudo-continuous ASL and control periods. Turbo-DASL experiments at 9.4 T, without and with diffusion gradients were performed on rats anesthetized with isoflurane or α-chloralose. We determined blood transit times from carotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 45 publications
3
12
0
Order By: Relevance
“…Our CASL MRI CBF values are similar to previous reports . Cortical CBF has been reported to be 0.74 mL/g/min by H 2 17 O MRI , 0.91 mL/g/min by flow‐sensitive alternating inversion recovery (FAIR) MRI and 0.85 mL/g/min by iodoantipyrine autoradiography .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our CASL MRI CBF values are similar to previous reports . Cortical CBF has been reported to be 0.74 mL/g/min by H 2 17 O MRI , 0.91 mL/g/min by flow‐sensitive alternating inversion recovery (FAIR) MRI and 0.85 mL/g/min by iodoantipyrine autoradiography .…”
Section: Discussionsupporting
confidence: 90%
“…In the MRI and PET literatures, subcortical CBF is overall smaller or similar to cortical CBF , as we observed in our study. Our microsphere data showed that striatal CBF by 8 μm microspheres was higher than that by MRI.…”
Section: Discussionsupporting
confidence: 88%
“…A further factor to be considered is that all experiments here were performed under isoflurane anesthesia. Isoflurane may increase baseline CBF , but have little or no effect on hypercapnic CBF response in normal rat brain. It is not known, however, whether isoflurane influences cerebral and tumor vasculatures differently.…”
Section: Discussionmentioning
confidence: 91%
“…Continuous ASL employs magnetic labelling, tagging, of arterial blood through the application of an up to seconds long inversion RF pulse to the cervical arteries (50,51). The magnetic inversion of the protons contained in the blood reaching the brain causes a marginal T1-signal loss that is harnessed in a so-called tag-image, and which is subsequently compared to a non-tagged control.…”
Section: Perfusion Weighted Imaging In Ischemic Strokementioning
confidence: 99%